Efektivitas Pembelajaran Daring terhadap Daya Serap Siswa Kelas 9 SMP Kristen Kanaan Jakarta - Wisnu Mursabdo; Michael Christian Mursabdo (Jurnal LENTERA: Jurnal Studi Pendidikan, 2021)
This study aims to determine the impact of online learning on students' absorption during online learning. This research is qualitative with the hope of providing an overview of students' conditions during online learning. The research method was conducted using an online survey involving 22 students from 60 students of SMP Kristen Kanaan Jakarta. From the results of the interviews, it can be drawn a picture that half of the students experienced problems in absorbing learning materials. Even half of the students also experience psychological stress due to online learning. The lack of social interaction between students and teachers becomes an obstacle in the absorption and understanding of teaching materials